Dynamic analysis and parametric control of ultrasonic vibration assistant machining system - Tan, Shao Wei. (2012)
Vibration assisted machining combines precision machining with the application of small-amplitude vibration to improve the machining process and achieve better surface quality. The periodic separation between the tool rake face and uncut material surface produces intermittent cutting, which reduces cutting tool forces, resulting in improved surface quality and also extended tool life. Previous investigations have been carried out to study the effect of application of one dimensional vibratory motion in the feed and cross feed directions. In this Final Year Project, 1D ultrasonic vibration assisted milling in the axial direction of the cutting tool is designed. Modal analysis is first simulated using the ANSYS® software to determine the natural frequencies of the tooling system used. Following which, milling tests are performed, and different machining parameters are investigated. These parameters include cutting tool diameter, direction of milling, spindle speed and feed per tooth. It is observed that a larger cutting tool diameter is able to produce better surface quality for the experimental setup used. In addition, down milling is able to produce better surface quality than up milling at higher spindle speed. Also, ultrasonic vibration assistance is observed to bring out lower surface roughness than conventional milling as feed per tooth increases. Some explanations are offered to support these results at the end of this report.